Endoparasitos de tucunaré-azul (Cichla piquiti, Cichlidae) e corvina (Plagioscion squamosissimus, Sciaenidae) em bacias hidrográficas nativas e invadida : testando a hipótese do escape do inimigo. - Lacerda, Ana Carolina Figueiredo (2011)
Biological invasions are considered a major threat to biodiversity around the world, but the role of parasites in this process is still little investigated. Here we tested the enemy release hypothesis (ERH), which explains part of the success of the invasive species by the loss of their native enemies (parasites and predators), using the endoparasites of the fishes Cichla piquiti and Plagioscion squamosissimus (Sciaenidae) in three Brazilian rivers: Solimões (SO), Tocantins (TO) and Paraná (PR). First, the parasites and their influence on the condition of the hosts in the native environment, the TO and also the SO for P. squamosissimus, were compared to an environment where the fish was introduced, the PR. Then, comparisons of the abundances of diplostomids and larval nematodes were made between the introduced fish and two predators native to the PR, Hoplias malabaricus and Raphiodon vulpinus. The use of GLMs with the relative condition factor of fish as response variables, and abundance of the most prevalent parasites as possible predictors showed that the condition of fish is negatively correlated with parasite abundance only in the native range (TO). For both introduced species, in the PR, abundance of Contracaecum sp. did not differ between natives and invaders; however, eye flukes were more abundant in the native fish H. malabaricus, which may represent an advantage to the invaders. Although P. squamosissimus may have lost most of its native parasites as predicted by the ERH, it is now acting as a host for native generalist parasites. A new nematode species found parasitizing C. piquiti from TO is described herein. It belongs to the genus Cucullanus and is characterized by having a posterior extremity provided with a sclerotized structure presenting spines on the ventral portion. The results do not support the idea that the escape from parasites favoured the establishment of C. piquiti nor P. squamosissimus in the PR. Instead, the escape from the parasites' effects seems a better explanation, and further studies examining effects on host physiology and/or fitness in the native and introduced ranges are needed.